2016
DOI: 10.1186/s12885-016-2947-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing conVEntional RadioTherapy with stereotactIC body radiotherapy in patients with spinAL metastases: study protocol for an randomized controlled trial following the cohort multiple randomized controlled trial design

Abstract: BackgroundStandard radiotherapy is the treatment of first choice in patients with symptomatic spinal metastases, but is only moderately effective. Stereotactic body radiation therapy is increasingly used to treat spinal metastases, without randomized evidence of superiority over standard radiotherapy. The VERTICAL study aims to quantify the effect of stereotactic radiation therapy in patients with metastatic spinal disease.Methods/designThis study follows the ‘cohort multiple Randomized Controlled Trial’ desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Prior uncontrolled studies using single-fraction SBRT for palliation of osseous metastases with doses of 15 to 24 Gy report high rates of in-field and symptomatic relief. 19 , 20 , 21 , 22 Our prior institutional report of patients with PCa with bone-only metastases demonstrated that ≥18 Gy in a single fraction resulted in superior metastasis control, with a potential increased benefit for lesions treated to >18 Gy (vs 18 Gy). 7 A multi-institutional analysis of oligometastatic, treatment-naïve PCa treated with SBRT demonstrated improved local control in patients treated with a BED of >100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior uncontrolled studies using single-fraction SBRT for palliation of osseous metastases with doses of 15 to 24 Gy report high rates of in-field and symptomatic relief. 19 , 20 , 21 , 22 Our prior institutional report of patients with PCa with bone-only metastases demonstrated that ≥18 Gy in a single fraction resulted in superior metastasis control, with a potential increased benefit for lesions treated to >18 Gy (vs 18 Gy). 7 A multi-institutional analysis of oligometastatic, treatment-naïve PCa treated with SBRT demonstrated improved local control in patients treated with a BED of >100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Effective systemic palliative treatment decreases the intensity of symptoms related to malignancies. The most effective of these is palliative radiotherapy, which brings about a very satisfactory local analgesic effect in 85% of patients, and a complete resolution of pain symptoms in about 15-60% of patients [7]. The analgesic effect, brought about as a result of the destruction of radiation-sensitive macrophages and osteoclasts, is independent of the histopathological type of cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes for the two groups are compared post-trial using the cohort’s routine data collection procedures. In most examples of cmRCTs, prior to enrolment in the cohort, patients are informed and consent to the possibility that they may be participants in trials but would not be notified about the trial if they are assigned to usual care 17–22…”
Section: Introductionmentioning
confidence: 99%